Feeling and Impact of Job Security on Level of Ambition Among Directors in the Palestinian National Authority Ministries' Headquarters - Nidal Sameer Nayef Ibrahim (My University, 2004)
This study aimed at identifying the relationship between the feeling of job security and level of ambition among directors of the Palestinian National Authority ministries' headquarters in the West Bank governorates. To this end, a random sample of directors in the ministries' headquarters was selected. The population of the study totaled 238 male and female directors. The study, in addition, sought to find out the role of the study variables on the relationship. For this purpose, the researcher used Maslow's and Abdel Fattah's Security and Ambition Level scales. The researcher tested validity of the scale. He also tested the reliability coefficient of Ambition scale as w0ell as the reliability coefficient of Feeling of Security scale. They were 0.79 and 0.87 respectively. After data collection, the research processed the data by using SPSS.Hypotheses of the study 1. There are no statistically significant differences at α = 0.05 level in the feeling of security and level of ambition among directors in the PNA's ministries' headquarters in the West Bank which may be attributed to sex variable. 2. There are no statistically significant differences at α = 0.05 in the feeling of security and level of ambition among directors in the PNA's ministries' headquarters in the West Bank which may be due to job title variable. 3. There are no statistically significant differences at α = 0.05 in the feeling of security and level of ambition among directors in the PNA's ministries' headquarters in the West Bank which may be due to last academic qualification obtained by director. The researcher found the degree of feeling security received a very low rating while the degree of ambition level received a high rating. It was also found that there was a correlation between feeling of security and level of ambition. The significance was α = 0.01. That is, the relationship was contrasting. In other words, the more feeling of security one had, the less level of ambition one had. No statistically significant differences in the feeling of security were found. However, there were differences in the level of ambition in favor of males. There were, however, no statistically differences in the level of ambition but there were differences in the feeling of security due to job title variable in favor of Director C, and department head. There were no statistically significant differences in the level of ambition but there were differences in the feeling of security due to the academic qualification variable in favor of those holding B.A., M.A. and Ph.D. In the light of the study findings, the researcher recommends the following: · Taking into consideration the feeling of security in the ministries' laws to create among directors the feeling of security and more seriousness in work in the ministries. · Enhancing the level of ambition among women directors in the PNA's ministries through promotions and training courses given their importance for them. · Increasing the feeling of security among directors in the Palestinian ministries particularly among those who have low academic qualification given its positive role in creating a conducive environment for work.

هدفت هذه الدراسة التعرف إلى العلاقة بين الإحساس بالأمن ومستوى الطموح لدى المدراء العاملون في مقرات وزارات السلطة الوطنية الفلسطينية بمحافظات الضفة الغربية، ولتحقيق هذه الأهداف اختيرت عينة الدراسة من المدراء في مقرات الوزرات وتكونت من 238 مدير ومديره، كما هدفت التعرف إلى دور متغيرات الدراسة، ولتحقيق هدف الدراسة استخدم الباحث مقياسي ماسلو وعبد الفتاح للأحساس بالامن ومستوى الطموح، وتم التاكد من صدقها، وبلغ معامل ثبات مقياس الطموح (0.79)، وثبات مقياس الاحساس بالامن (0.87)، وبعد عملية جمع الاستبانات تم معالجتها احصائيا باستخدام الرزمة الاحصائية للعلوم الاجتماعية (SPSS) وحاولت الدراسة فحص الفرضيات الاتية: لا توجد فروق ذات دلالة احصائية عند مستوى الدلالة ( α= 0.05) في كل من الاحساس بالامن ومستوى الطموح لدى المدراء العاملون في مقرات وزارات السلطة الوطنية الفلسطينية بالضفة الغربية تعزى لمتغير الجنس، والرتبة الوظيفية، والمؤهل العلمي وتمخضت النتائج عن الاتي : ان درجة الاحساس بالامن حصلت على تقدير منخفض جدا، ودرجة مستوى الطموح حصل على تقدير مرتفع . توجد علاقة ارتباطية بين الاحساس بالامن ومستوى الطموح حيث كانت دالة إحصائياً عند مستوى الدلالة (0.01) انه توجد علاقة عكسية اي انه كلما قل الاحساس بالامن قل مستوى الطموح. لاتوجد فروق دالة احصائيا في الاحساس بالامن ووجدت فروق في مستوى الطموح حيث كانت الفروق لصالح الذكور . لاتوجد فروق دالة احصائيا في مستوى الطموح بينما كانت وجدت فروق على الاحساس بالامن تبعا لمتغير المركز الوظيفي، ولصالح مدير C، رئيس قسم. لاتوجد فروق دالة احصائيا في مستوى الطموح بينما كانت وجدت فروق على الاحساس بالامن تبعا لمتغير المؤهل العلمي ولصالح حملة مؤهل البكالوريوس،و الماجستير،و الدكتوراة. في ضوء نتائج الدراسة اوصى الباحث بالاتي: -مراعاة الشعور بالأمن في قوانين الوزارات لكي يخلق عند المدراء الاطمئنان والامن والطمأنينة والعمل بجد أكثر في الوزارة. - تدعيم مستوى الطموح لدى المديرات في وزارات السلطة من خلال الترقيات والدورات التدريبية لما لها من أهمية لدى المديرة. -زيادة الشعور بالأمن للمدراء في الوزارات الفلسطينية وبخاصة من ذوي المؤهلات العلمية المنخفضة لما له من دور ايجابي بخلق مناخ مشجع للعمل.
الأمن الوظيفي و علاقته بمستوى الطموح لدى المدراء العاملين في مقرات وزارات السلطة الوطنية الفلسطينية واثر بعض المتغيرات الديمغرافية عليهما